Right ventricular dysfunction secondary to hyperthyroidism with total reversal after thyroidectomy: case report - Rosa Filho, Alfredo Aurélio Marinho; Peixoto Menezes, Gabriela Serpa; Ferro, Carlos Romério Costa (Brazilian Journal of Case Reports, 2023)
Thyrotoxicosis is a condition caused by an increase in thyroid hormone, commonly associated with Graves’ disease and toxic multinodular goiter. Hyperthyroidism is known to increase the risk of pulmonary hypertension and right heart failure, although the underlying mechanisms are still unclear. The identification of these conditions is crucial, as they are potentially reversible with the achievement of euthyroidism. This case report describes a 40-year-old woman with right ventricular dysfunction and pulmonary hypertension due to hyperthyroidism, which was successfully treated with total thyroidectomy. The case highlights the importance of considering thyrotoxicosis as a potential cause of pulmonary hypertension and the need to rule out other underlying causes. Echocardiography is a valuable tool in assessing right ventricular dysfunction, and achieving euthyroidism can result in the reversal of structural and functional cardiac alterations.